Bandwidth Broker based admission control for guaranteed video quality of experience - Luo, Wuqiong. (2010)
The current Best Effort service in the Internet will not be able to cater for the increasingly demand of high bandwidth real-time video traffic. Many possible mechanisms have been proposed to provide QoS guarantees to individual traffic streams. However, the scalability and complexity issues remain unresolved. In this report, a novel Bandwidth Broker architecture based scalable QoS provisioning mechanism called Scalable MultiServ is presented. This framework provides different classes of QoS with different queuing delay bounds on top of the current Best Effort delivery service in a network so that video users may enjoy acceptable quality of experience. In our comprehensive solution, routers do not need to maintain any QoS reservation states and the computation complexity is pushed to end users, leaving simple priority scheduling at all routers, thereby addresses scalability and complexity problems. Admission Control and Domain QoS States Database system is designed for the proposed Scalable MultiServ mechanism. The performance of the architecture is evaluated by means of NS-2 simulations.